Stayers and returners: Educational self-selection among US immigrants and returning migrants - Arturo Alberto Aguilar Esteva (Institute for the Study of Labor (IZA), 2013)
This paper empirically examines the educational selectivity of United States immigrants and of those that return to their source country. Data from the 1970 to 2000 U.S. Census and the 2010 American Community Survey are employed. Ten countries are selected for the study based on their historical and contemporaneous importance on U.S. migration. The results generally indicate positive selection on educational attainment of recently-arrived immigrants, being China, India, and Philippines the most prominent examples. Mexico does not show evidence of positive or negative selection, but their immigrants' selectivity has worsened through time. Historically, the educational selectivity of returning migrants accentuated the positive selection of those migrants that stay in the United States in most countries' cases. However, patterns of selection among migrants that stay have recently changed. A more detailed analysis with data from the last decade finds evidence of positive selection of immigrants staying in the U.S. for the Mexican and Philippines' case, as well as negative selection for the Chinese. Trends of returning migration are also analyzed by gender, age, naturalization status, and migration spell duration. Mixed evidence of selection trends is found.
Keywords: I25; J11; J61; 330; immigration; return migration; self-selection; education